A STUDY ON THE EPIDEMIOLOGY OF HELMINTHS OF BUFFALOES IN IRAQ - H. Kaid, L.; I. Altaif , K. (The Iraqi Journal of Veterinary Medicine, 1990)
A study on the epidemiology of helminths of buffalloes, conducted at two different areas, revealed the followings; Three species were reported for the first time in Iraq; Moniezia benedeni, Gastrothylax crumonifer and Carmyerius spatiosus. In both areas high rates of observed. The infection with Fasciola gignatica was study further revealed a higher rate of infection with fertile systs in the lungs than in livers. There was a good correlation between the environ- mental factors and parasitic infections in both provinces.